How to earn dollars overseas - Andres, Tomas Quintin D. (New Day, 1994)
This book contains realistic advice combined with creative attitudes and techniques for overseas job seekers. It not only provides instructions on learning about available overseas jobs but also gives facts and data about conditions abroad and how to cope with loneliness and "culture shock" once they are there.